A PSIKOEDUKASI DETEKSI DINI ANAK DENGAN GANGGUAN PEMUSATAN PERHATIAN DAN HIPERAKTIF (GPPH) PADA GURU DAN ORANGTUA - Hapsari, Iriani Indri; Ariani, Dewinta; Hizbullah, Kahfi (Jendela Akademika, 2025)
This community service program aims to enhance early detection skills of teachers and parents in identifying Attention-Deficit Hyperactivity Disorder (ADHD) or GPPH in children. ADHD is a neurodevelopmental disorder marked by inattention, hyperactivity, and impulsivity, which can significantly impact a child's academic, social, and emotional development. The main issue identified at SDIT An-Nur, Bandung, was the lack of awareness and knowledge among educators and parents regarding ADHD symptoms and intervention strategies. To address this, a psychoeducation program was conducted involving lectures, interactive discussions, and practical observation training. Participants completed a pre-test and post-test to measure knowledge improvement. The program also introduced a pocket guidebook as a reference for ongoing learning. Results showed a significant increase in understanding and awareness among participants, with active engagement during discussions indicating their motivation to support children with ADHD. This program highlights the importance of early detection through collaborative efforts between schools and families, contributing to inclusive mental health promotion aligned with SDG 3 (Good Health and Well-being).